2019
DOI: 10.20411/pai.v4i2.338
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Immunogenicity of the DS-Cav1-Stabilized Fusion Glycoprotein From Respiratory Syncytial Virus Subtype B

Abstract: Background:Respiratory syncytial virus (RSV) subtypes, A and B, co-circulate in annual epidemics and alternate in dominance. We have shown that a subtype A RSV fusion (F) glycoprotein, stabilized in its prefusion conformation by DS-Cav1 mutations, is a promising RSV-vaccine immunogen, capable of boosting RSV-neutralizing titers in healthy adults. In both humans and vaccine-tested animals, neutralizing titers elicited by this subtype A DS-Cav1 immunogen were ~ 2- to 3-fold higher against the homologous subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…This is likely due to the conservation of a small polar, uncharged side chain for both A and B strains, thus maintaining a similar environment for recognition by RSB1. On the other hand, the Asp200Asn substitution would likely result in the loss of a salt bridge with RSB1 Arg53 LCDR2 (Fig 2D), and comparison with the RSV B structure (PDB 6Q0S) [40] indicates there would be a shift in the local surface potential from a negatively charged region into a more neutral or positive surface (S6 Fig) . This would seemingly disfavor binding to the RSB1 positively charged Arg53 LCDR2 . However, we found that the single mutant Asp200Asn, as well as the double mutant Asp200Asn-Asn276Ser, were again not sufficient to impact the binding affinity for RSB1.…”
Section: Molecular Basis For Breadth Of Rsb1 Neutralizationmentioning
confidence: 99%
“…This is likely due to the conservation of a small polar, uncharged side chain for both A and B strains, thus maintaining a similar environment for recognition by RSB1. On the other hand, the Asp200Asn substitution would likely result in the loss of a salt bridge with RSB1 Arg53 LCDR2 (Fig 2D), and comparison with the RSV B structure (PDB 6Q0S) [40] indicates there would be a shift in the local surface potential from a negatively charged region into a more neutral or positive surface (S6 Fig) . This would seemingly disfavor binding to the RSB1 positively charged Arg53 LCDR2 . However, we found that the single mutant Asp200Asn, as well as the double mutant Asp200Asn-Asn276Ser, were again not sufficient to impact the binding affinity for RSB1.…”
Section: Molecular Basis For Breadth Of Rsb1 Neutralizationmentioning
confidence: 99%
“…3c ; also ref. 52 ]. This is notable because escape mutations to D25 have been identified in infants who suffered a breakthrough infection with RSV subtype B after receiving nirsevimab 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the ultrastructural arrangement and dynamics of Gn and Gc on the surface of the virion and how that may contribute to the exposure or occlusion of important antigenic sites is critical in development of medical countermeasures. For example, understanding the antigenic sites exposed in the respiratory syncytial virus (RSV) F protein and molecular determinants of prefusion stabilization has led to the development of a highly immunogenic RSV vaccine (63). Most recently, knowledge of the molecular-level dynamics of the receptor binding domain (RBD) in coronaviruses gave way to the rapid development of a prefusion stabilized spike protein vaccine that exposes immunogenic sites in the "up" form of the RBD (64).…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 99%